The Effect Of Hypnopuncture On Stress Response In Final Students In The Pandemic Era Of COVID-19 - Franciscus Xaverius, Franciscus Xaverius; Purwanto; Jatmiko, Rinto Wahyudi; Nisa, Riatun (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
At the end of 2019, the world was shocked by the emergence of a new virus, SARSCoV-2 which causes COVID-19. Changes that occur in students due to COVID-19 certainly have an impact on student psychology. Hypnopuncture is a combination method of Hypnosis and Acupuncture therapy, which is expected to be effective in dealing with health complaints. The purpose of this study was to determine the effect of Hypnopuncture on stress response in final year students in the era of the COVID-19 pandemic.This research was conducted at STIKes Cirebon, in September 2020-March 2021. This research is a Quasy experiment with pretest and posttest design. The sample in this study was final year students at STIKes Cirebon, which was 43 students.T-test dependent or Paired Sample T-test can be known the level of significance in reducing student stress levels. The results of the Paired Sample T-test on the pretest and postest obtained a value of ρ <0.000, so there is an influence of hypnopuncture on stress in final year STIKes Cirebon students. Hypnopuncture therapy using a combination of hypnosis and acupuncture affects stress in final year STIKes Cirebon students.